The relationship between organizational stressors and athlete burnout in soccer players - Tabei, Y.; Fletcher, D.; Goodger, K. (7th World Congress on Science and Football (WCSF), 2011, 2011)
Although researchers have begun to uncover the causes of the organizational stress process in sport, little is known about the potential consequences and outcomes, including burnout. In competitive soccer, considerable stress exists, exposing many players to a chronic level of stress which can lead to burnout. Therefore, this study investigated the relationship between organizational stressors in sport and athlete burnout, and involved a cross-cultural comparison of English and Japanese soccer players. Method 98 male collegiate soccer players (English = 50, Japanese = 48) aged 18-23 years (M = 20.19, SD = 1.20) completed the Athlete Burnout Questionnaire (ABQ; Raedeke & Smith, 2001) to determine levels of perceived burnout. Interview procedure was followed to explore the relationship between organizational stressors and the dimensions of burnout. The interview sample comprised 9 participants (English = 5, Japanese = 4) aged 20-22 years (M = 20.89, SD = 0.60) and they all scored above thresholds (Hodge, Lonsdale, & Johan., 2008) on ABQ. Results & Discussion Using the thresholds of burnout, burnout was prevalent in 22.45% of English (6 of 50) and Japanese (16 of 48) collegiate soccer players. Overall, the Japanese players reported higher perceived burnout across all dimensions. Results revealed multiple demands and specific organizational-related issues that players associated with the incidence and the dimensions of burnout. Cultural differences between English and Japanese players in terms of the prevalence and organizational stressors associated with burnout were also identified, with the main differences being the coaching style and the relationship with senior teammates. Conclusion It can be concluded that organizational variables affect the burnout levels experienced by soccer players. We posit that there is a need for psychology consultants and those who have power in an organization such as coaches and managers to develop and acquire specific abilities to manage the potential impact of organizational stress on athletes. Athletes have little power to effect organizational changes in sport. Therefore, for effective and long-term alleviation of burnout, fundamental changes in sport organizations and organizational environments may be essential to reduce the exhaustion experienced by athletes. In addition, there is a need for further investigations to explore and deeply understand how the sport cultures impact burnout.